Multi-duties for one post: Biodegradable bacterial cellulose-based separator for lithium sulfur batteries. (1st June 2022) - Wu, Shuanglin; Shi, Jiayi; Nie, Xiaolin; Yu, Zhifeng; Huang, Fenglin
Abstract: High-energy density lithium sulfur battery containing highly active materials is more prone to safety hazards. Besides, the infamous shuttle effect of lithium polysulfides (LiPSs) and listless redox kinetic limit its practical applications. Here, a "one-for-all" design concept for separator enabled by interfacial engineering is proposed to relieve the bottlenecks. For one thing, porous bacterial cellulose (PBC) membrane with high thermostability (no shrinking at 200 °C) and puncture resistance was employed to ensure the battery's safety. For another, a difunctional Ti3 C2 Tx -SnS2 modified layer could capture LiPSs through lewis-acid interaction and promoted the redox kinetics by catalytically active sites. The symmetric cell with anchoring-electrocatalysis Ti3 C2 Tx -SnS2 -PBC separator infiltrated with the electrolyte delivered an ionic conductivity of 2.171 mS/cm at a high temperature of 180 °C. And a capacity retention is improved by 71.2% compared with PP separator. This work furnishes a facial engineering strategy for manufacturing a multifunctional separator for lithium sulfur batteries. Graphical abstract: Unlabelled Image